1994
DOI: 10.1148/radiology.190.3.8115607
|View full text |Cite
|
Sign up to set email alerts
|

Hill-Sachs lesion and normal humeral groove: MR imaging features allowing their differentiation.

Abstract: A Hill-Sachs lesion is best differentiated from the anatomic groove by means of its more cephalic position along the longitudinal humeral axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…55,56 Managing these defects involves restoring bone anatomy to restore the concavity-compression model or converting intraarticular pathologies to extra-articular ones. Arthroscopic techniques are evolving to address acute and chronic glenoid defects 45,49,[57][58][59] ; however, open techniques are usually preferred.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…55,56 Managing these defects involves restoring bone anatomy to restore the concavity-compression model or converting intraarticular pathologies to extra-articular ones. Arthroscopic techniques are evolving to address acute and chronic glenoid defects 45,49,[57][58][59] ; however, open techniques are usually preferred.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…Therefore, shearing against the glenoid rim with concomitant impression or depression fracture seems to be a more convincing mechanism as a cause of greater tuberosity fractures. This theory is further supported by the study of Richards et al 43 They identified the Hill-Sachs lesion in the lateral aspect of the intraarticular portion of the humeral head, as well as in the posterior part of the greater tuberosity. The exact position is determined by the degree of rotation of the humeral head during the injury.…”
Section: Discussionmentioning
confidence: 71%
“…At CT or MR imaging, a Hill-Sachs lesion should be differentiated from the normal groove that is found at the posterolateral humeral head but more inferiorly. All Hill-Sachs lesions occur within the superior 4-5 mm of the humeral head margin, which should otherwise be circular on axial CT or MR images (Fig 13a) (28). Meanwhile, the normal longitudinal groove on the posterolateral humeral neck (Fig 13b, 13c) is located 20-38 mm below the superior aspect of the humeral head (28).…”
Section: Anterior Shoulder Dislocationmentioning
confidence: 99%